2009
DOI: 10.3892/or_00000269
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced apoptosis in human breast cancer MCF-7 cells through caspase-independent pathway

Abstract: Abstract. , a significant pungent ingredient in a variety of red peppers of the genus Capsicum, is a type of vanilloid. It has been shown to exert biological activities (anticarcinogenic, antimutagenic and chemopreventive) in many cancer cell lines. It was found that capsaicin induces dose-dependent growth inhibition of MCF-7 cells, which does not express caspase-3. In this study, we investigated the molecular mechanism of capsaicin-induced apoptosis in MCF-7 cells. Treatment with capsaicin for 24 h resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The fragments were in oligonucleosome size, which could be approve of apoptotic induction by capsaicin treatment in HepG2 cells. Our results are in agreement with Cho et al [5] stated that MG63 human osteosarcoma cells were cultured for 24h with different concentrations of capsaicin, the cells exhibited the morphological features of apoptosis when treated with 150µM capsaicin for 24h. These morphological changes of the cells represent the apoptotic cell death [18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fragments were in oligonucleosome size, which could be approve of apoptotic induction by capsaicin treatment in HepG2 cells. Our results are in agreement with Cho et al [5] stated that MG63 human osteosarcoma cells were cultured for 24h with different concentrations of capsaicin, the cells exhibited the morphological features of apoptosis when treated with 150µM capsaicin for 24h. These morphological changes of the cells represent the apoptotic cell death [18].…”
Section: Discussionsupporting
confidence: 93%
“…In recent findings, capsaicin is seen to show anti-proliferative effects on various human cancer cell lines by apoptosis mediated cell death [4]. Diverse studies have shown that capsaicin has anti proliferative effect on several human cell lines derived from multiple myeloma, gastric cancer, pancreatic cancer, breast cancer [5] and prostate cancer [6], etc. However, the molecular mecha¬nisms underlying capsaicin-induced apoptosis are cell type dependent: capsaicin induces apoptosis in sensory neurons by increasing calcium influx and does so by activating vanil¬loid receptors in some transformed cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al studied the anticancer activity of capsaicin against breast cancer and concluded that the mechanism could be related to the down-regulation of the FBI-1-mediated NF-κB pathway [35]. The anticancer activity of capsaicin can also be related to the caspase-independent pathway [36]. Thus, the inhibition of Aurka can be one of the new possible anticancer mechanisms of the compounds obtained from peppers.…”
Section: Resultsmentioning
confidence: 99%
“…435 Expectedly, artesunate synergistizes with sorafenib to induce ferroptosis in HCC and non-Hodgkin lymphoma cells. 436,437 Consistently, dihydroartemisinin, the metabolite of artemisinin, 438 inhibits lung cancer cells by suppressing the PRIM2/SLC7A11 axis, 439 and enhances the cytotoxicity of gefitinib in LUAD cells, 440 sorafenib in HCC, 441 and cisplatin in PDAC. 442 Haloperidol, a specific antagonist of dopamine receptor D2 (DRD2) extensively used for the treatment of psychiatric disorders, 443 exhibits inhibitory effects in cancers by inducing ferroptosis.…”
Section: Systemic Drugsmentioning
confidence: 90%